Study on the Phosphate Compound Adsorption onto MgO-KOH/Biochar Adsorbent as Binding Agent in Diffusive Gradient in Thin Film (DGT) Technique for Bioavailable Phosphate Detection - Permatasari, Indah; Saefumillah, Asep (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Phosphate compounds, particularly bioavailable forms like PO₄³⁻, are critical contributors to eutrophication. In this study, MgO-KOH/biochar was used as a binding agent in the Diffusive Gradient in Thin Films (DGT) technique to enhance phosphate detection. The adsorbent was synthesized from biochar derived from palm oil waste, activated with KOH to increase surface area, and combined with MgO for enhanced adsorption efficiency. The adsorption process followed a pseudo-second-order kinetic model, indicating that chemical interactions dominated the adsorption mechanism. Under different pH levels and phosphate concentrations, the material showed a good selectivity for orthophosphate, achieving an adsorption capacity of approximately 100 mg/g. Characterization via FTIR, XRD, and SAA confirmed the successful synthesis of MgO-KOH/biochar and its structural properties, which contributed to its performance. Additionally, the MgO-KOH/biochar DGT device demonstrated better efficiency in adsorbing PO₄³⁻ compared to conventional ferrihydrite-based DGT systems, positioning it as a highly effective tool for monitoring bioavailable phosphates in aquatic environments. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).